Caught in the cross fire: p53 in inflammation - Cooks, Tomer (Oxford University Press, 2014)
The p53 transcription factor is a major tumor suppressor, whose diverse activities serve to ensure genome stability and inhibit neoplastic processes. In recent years, it is becoming increasingly clear that p53 also plays a broader role in maintaining cellular homeostasis, as well as contributing to tissue homeostasis in a non-cell-autonomous fashion. Chronic inflammation is a potential cancer-promoting condition, and as such is also within the radar of p53, which mounts a multifaceted attempt to prevent the escalation of chronic tissue imbalance into neoplasia. Recent understanding of the p53 pathway and other family members reveals a broad interaction with inflammatory elements such as reactive oxygen and nitrogen species, cytokines, infectious agents and major immune-regulatory pathways like nuclear factor-kappaB. This complex cross talk is highly dependent on p53 status, as different p53 isoforms and p53 mutants can mediate different responses and even promote chronic inflammation and associated cancer, acting in the tumor cells as well as in the stromal and immune compartments.